Tailoring Immune Responses toward Autoimmunity: Transcriptional Regulators That Drive the Creation and Collusion of Autoreactive Lymphocytes - Good-Jacobson, Kim L.; Groom, Joanna R. (Frontiers in Immunology, 2018)
T-dependent humoral immune responses to infection involve a collaboration between B and CD4 T cell activation, migration and co-stimulation, culminating in the formation of germinal centers (GC) and eventual differentiation into memory cells and long-lived plasma cells. CD4 T cell-derived signals drive the formation of a tailored B cell response. Downstream of these signals are transcriptional regulators that are the critical enactors of immune cell programs. In particular, a core group of transcription factors regulate both B and T cell differentiation, identity and function. The timing and expression levels of these transcription factors are tightly controlled, with dysregulated expression correlated to immune cell dysfunction in autoimmunity and lymphomagenesis. Recent studies have significantly advanced our understanding of both extrinsic and intrinsic regulators of autoreactive B cells and antibody-secreting plasma cells in systemic lupus erythematosus, rheumatoid arthritis and other autoimmune conditions. Yet, there are still gaps in our understanding of the causative role these regulators play, as well as the link between lymphoid responses and peripheral damage. This review will focus on the genesis of immunopathogenic CD4 helper and GC B cells. In particular, we will detail the transcriptional regulation of cytokine and chemokine receptor signalling during the pathogenesis of GC-derived autoimmune conditions in both murine models and human patients.